If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = u + -6 Reorder the terms: 13 = -6 + u Solving 13 = -6 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. 13 + -1u = -6 + u + -1u Combine like terms: u + -1u = 0 13 + -1u = -6 + 0 13 + -1u = -6 Add '-13' to each side of the equation. 13 + -13 + -1u = -6 + -13 Combine like terms: 13 + -13 = 0 0 + -1u = -6 + -13 -1u = -6 + -13 Combine like terms: -6 + -13 = -19 -1u = -19 Divide each side by '-1'. u = 19 Simplifying u = 19
| -13+12(7)= | | 2(b+3)=14 | | 5p=-8+6p | | 18s-11s-5s=20 | | 4(7s+3)=-15 | | -194-7x=3x+66 | | 2h=1.5h(15*2) | | 54=6+6x | | -4n-4=-56 | | -3s=-135 | | -30+2x=6x+18 | | n*n+8n+2= | | 18=4(s-13) | | (x-8)(4x+2)=10x(x-8) | | 3.69+49=13.6161+7x | | 7v=-350 | | -37-8x=-11x+14 | | 9=3(t+14) | | 7x+16=2x | | 13=-4 | | 8=4(y-18) | | -7x-8=8 | | 5b=-10+6b | | 28x+11=1 | | 2y^3=0 | | 7x+5=9z-5 | | 8v=-344 | | k+-15k+7=-7 | | 5b=200 | | 6cos(x)-4=0forx | | 6*cos(x)-4=0 | | x^2+px-9=(x-1)(x+q) |